Meningkatkan Kesadaran dan Partisipasi Pengrajin Batik dalam Melestarikan Nilai-Nilai Budaya Lokal - Jamahari Jamahari; M.Taufik Ullatif; Nur Fadilah; Aribatul Istiqamah; Erni Septia Ningsih; Novi Fitria; Muhammad Khairurrizal; Saifudin Fauzy; Risti Ananda Safitri; Dinda Aulia; M Rusli; Mubarak Mubarak; Nur Azizah; M Nasir; Umi Latifah; Atika Atika; Wahyu Ramadhan; Nur Saidah Salsabilla; Abd Khanan Maksum (khidmatan, 2026)
This community service program aims to strengthen the role of batik artisans as creative economy actors in preserving Tanjung Pasir batik as a local cultural heritage. The program was conducted in Tanjung Pasir Village by involving batik artisans as the main partners, supported by community leaders, village government, and local MSME actors. The method applied was Participatory Action Research (PAR), which emphasizes active community involvement throughout all stages of the program, including condition and potential mapping, action planning, mentoring implementation, as well as evaluation and reflection. Data were collected through participatory observation, in-depth interviews, and activity documentation. The data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that the PAR approach enhances awareness and participation of batik artisans in preserving local cultural values reflected in the production process and philosophical meaning of Tanjung Pasir batik. This program is expected to contribute to the strengthening of culture-based creative economy development.